ASSESSMENT OF THE KNOWLEDGE AND USE OF BRIQUETTES FOR CLIMATE CHANGE OPTION AMONG RICE PROCESSORS IN ANAMBRA STATE, NIGERIA - Chukwujekwu A., Obianefo; Benjamin C., Okoh; Cecilia A., Nwigwe; Oluchi O, Anumudu; Funmilayo A, Toyin (Covenant Journal of Entrepreneurship, 2020)
The study on the assessment of the knowledge and use of briquettes for climate change option among rice processors in Anambra State, Nigeria investigated the level of rice processor’s knowledge and perception on the use of briquettes, perceived advantages of renewable energy, as well as the socio-economic characteristic influence on the processor’s perception and the perceived challenges to the production of briquettes. Data were collected from 974 randomly selected rice processors and analyzed with descriptive statistics and Tobit regression model. The study shows that the majority (62.2%) of the processors are female with mean age, processing experience and a monthly output of 43 years, 15 years and 4.5 tons respectively. Also, the processors were fairly knowledgeable on the use of briquettes but perceived renewable energy as economically viable, and climate-smart among others. The socioeconomic variables influencing their perception were Age, marital-status, enterprise size, experience, monthly income, and rice residues. Finally, the likely challenges that will constrain briquettes production include; high initial cost, high maintenance cost etc. furthermore, policymakers must swing into action to sensitize processors on the need to adopt renewable energy for environmental sustainability.